A operação diagnóstica em psicanálise: um ensaio sobre os conceitos de sintoma e transferência na composição de hipóteses diagnósticas em estruturas neuróticas - Rodrigues, Tatiana Gassen (2019)
Since Freud, the concern to establish valid diagnostic hypotheses is essential for clinical work, as it bases the whole process of intervention and therapeutic conduct. In psychoanalysis, this is a complex process that takes into account different factors and does not have a unique status, being understood and translated from different theoretical and technical sieves, according to the psychoanalytic strand. In any case, the question of diagnosis remains central to psychoanalysis; and this work seeks to contribute to the understanding of the diagnostic operation in the field of neuroses, considering freudian texts and current authors of psychoanalysis, contemplating as two basic criteria to make a diagnosis in psychoanalysis the analysis of the symptom and of transference. I use fragments of clinical materials to illustrate how these hypotheses are compounded in psychoanalytic clinic and I try to deepen the understanding of these domains – symptom and transference – to use them as parameters to place neuroses in the conceptual psychoanalytic scheme of elaboration of diagnostic hypotheses, as well as to delimit its specificity within psychoanalysis as an operation, which implies a composition of elements that act as guides for the treatment, making the therapeutic strategy more accurate and, therefore, being part of the therapy itself